HUBUNGAN KARAKTERISTIK ITERNAL INDIVIDU DENGAN KEPUASAN PTERHADAP PROGRAM TALKSHOW UKM DI RRI BATAM - Anggrayni, Dewi (JURNAL DIMENSI, 2013)
A small medium micro  enterprises  is the most resistant to the economic crisis as a small business is able to survive in the mid business high competition . In the era of free trade Small Medium Enterprises (SMEs) into alternative buffer belt of the nation's economy. In a free market opens  a challenge and an opportunity that is very promising for the development of SMEs in Batam. As a business unit, SMEs in view of need to increase the capacity and competitiveness of SMEs fellow in Batam as well as in other areas. Positive competition among SMEs will encourage owners of capital to innovate and inculcate product shares towards business opportunities that allows rapid turn-around of their money back. Product quality challenges ahead in order to compete with foreign products which entering the country.In business development, promotion is an effective tool for introducing the product. Further interest in the promotional products market is done will be the target for Entrepreneurs. So it is important for business owners are to choose the right promotional media. Radio is one of the effective promotional tools. In the development of SMEs, selecting a local radio as a promotional tool which effective and affordable. Radio broadcasting as a frequent media interface in the everyday life (Prayudha, 2004).Radio is expected to not only provide entertainment, but also can provide information that can be received and used the audience for productive activities, while enhancing public knowledge, so that by itself is expected to be more critical of community development program. This is increasingly important in line with the more intense attempts utilizing radio as a means of communication and media development in Indonesia.Radio program not merely convey information, but can be interesting, even indirectly to direct the behavior of the audience. Therefore, the radio can be used as promotional tools that play a role in improving public services. With the assistance of an interesting narrative advertisement or promotion of the product in the form of talk shows, SMEs as businesses will benefit by using the radio as a promotional tool. When acting as a resource whose role is to provide information to the public services, SMEs must be able to meet the needs of listeners, so the impact on the listener satisfaction for SMEs services. Radio through specific programming also serves as a place to collect and convey the needs of the market for the SMEs’ products.